Computational and experimental simulation to analyze loss in concrete cover by reinforcement deformation in solid slabs - Maran,Ana Paula (2022)
ABSTRACT Adequate cover thickness contributes to the correct performance of reinforced concrete structures. Spacers are recommended in standards to maintain a concrete cover; however, many regulations do not provide sufficient guidelines for their use, resulting in poor construction. A research program was developed for solid slabs through computational and experimental simulations to minimize errors in the cover by assessing different reinforcement bar diameters and spacer distribution, considering realistic element construction and standards, combining theory with practice. The results show that the use of spacers does not guarantee the design cover for some reinforcement bar diameters, as 4.2 and 5.0 mm, and regardless of the spacer distribution configuration assessed, these meshes undergo permanent deformation, thereby damaging the cover and consequently impact structural performance. Meshes of 6.3 and 8.0 mm diameters present deformation within the cover tolerance. Therefore, it is preferable to choose bigger diameters and larger mesh spacing to guarantee the projected cover, contributing to the correct performance of the structures, solving one of the major problems in this type of construction.